KEMITRAAN DALAM PENDIDIKAN ANAK USIA DINI (Analisis terhadap Pola dan Tingkah Laku Anak Usia Dini dan Lingkungan) - Hafidzi, Anwar; Putri, Hadisa (Jurnal Edukasi AUD, 2018)
Abstract: Partnership is a cooperative relationship between several parties in achieving a certain work relationship. The partnership between the school and the family and community in building an educational ecosystem is in line with the Ministry of Education and Culture's vision of "the formation of education and cultural   human   beings   with   character   based   on   mutual cooperation". This partnership also aims to establish cooperation and alignment of educational programs in PAUD units, families, and communities  as  a  center  of  education  in  building  a  quality education   ecosystem.   Therefore,   it   is   necessary   to   have   a relationship or involvement from all parties to achieve the development of quality education for early childhood. Abstrak: Kemitraan merupakan hubungan kerjasama antara beberapa pihak dalam mencapai suatu hubungan kerja tertentu.Kemitraan  antara  sekolah  dengan  keluarga  dan masyarakat dalam membangun ekosistem pendidikan sejalan dengan visi Kementrian Pendidikan dan Kebudayaan yaitu “ terbentuknya insan serta ekosistem pendidikan dan kebudayaan yang berkarakter dengan berlandaskan gotong royong”. Kemitraan ini juga bertujuan untuk menjalin kerjasama dan keselarasan program pendidikan di satuan PAUD, keluarga, danmasyarakat sebagai tri sentra pendidikan dalam membangun ekosistem pendidikan yang bermutu. Maka dari itu perlu adanya hubungan atau keterlibatan dari semua pihak untuk mencapai pengembangan pendidikan bagi anak usia dini yang lebih berkualitas.